Hemoperitoneum in Pregnancy: A Case Series and Clinical Management Insights - Purnama , Dean Reza; Aliah, Julyta; Indra , Indra (CoinReads Media Prima, 2025)
Introduction: Hemoperitoneum in pregnancy is a rare but life-threatening obstetric emergency characterized by intraperitoneal bleeding, often due to vascular rupture, uterine anomalies, or adnexal pathology. Its nonspecific symptoms, including acute abdominal pain and hemodynamic instability, complicate timely diagnosis, requiring rapid intervention to prevent severe maternal and fetal complications. Case Description: A 22-year-old primigravida at 28 weeks presented with acute abdominal pain, hypotension, and fetal distress on cardiotocography. Ultrasonography showed intraperitoneal free fluid, and emergency laparotomy revealed a ruptured uterine artery with 900 mL of blood. Surgical ligation and transfusion of two units of packed red cells achieved hemostasis, followed by cesarean delivery of a viable preterm neonate (1,200 g, Apgar 7/8). Nifedipine tocolysis stabilized the mother, discharged on day 7 with hemoglobin at 10.8 g/dL; the neonate required intensive care. The second case involved a 24-year-old primigravida at 28 weeks with hypotension (90/60 mmHg), tachycardia (120 beats/min), and similar ultrasound findings. Laparotomy showed a ruptured uterine vein with 800 mL blood, managed by ligation and transfusion of two packed red cell units. Nifedipine (20 mg every 6 h) prevented preterm labor, and pregnancy continued to term, delivering a healthy 3,200 g neonate (Apgar 8/9). The mother recovered well, with hemoglobin at 11.0 g/dL by day 7. Conclusion: This case highlights the critical need for swift ultrasonography and multidisciplinary management, including emergency surgery, to optimize outcomes in hemoperitoneum during pregnancy. Clinicians must maintain a high index of suspicion for acute abdomen with hypovolemia to prevent catastrophic maternal and fetal consequences.